The reaction of slaughter hog cash and futures prices to USDA hogs and pigs reports - Schroeder, Ted C.; Mintert, J.R.; Blair, John M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study examined the reaction of slaughter hog cash and futures prices to USDA Hogs and Pigs reports. Over the 1972-87 period, the nearby live hog futures price had $1/cwt or larger absolute price changes on 48% of the trading days immediately after the Hogs and Pigs report release compared to 6% of the days of the release, suggesting that the reports arc providing important new information to the market. Average price moves in cash and futures markets following the report releases were positive, suggesting that price usually increased the day after the reports. Over the 1972-87 period, the cash price declined on only 38% of the first trading days after the report releases, and the futures market price declined on 43%. The day of the week on which the Hogs and Pigs reports were released had no significant impact on the market's price variability following release.
Keywords: USDA hogs and pigs reports; Futures market; Price movements